A Feasibility study of creating a website for Chinese-literate women in the Philippines - Gao, Lan
"This study aims to determine the need for, and assess the feasibility of, creating a website for Chilnese-literate women in the Philippines. Drawing inspiration from computer-Mediated Communication theory, the Information Society Theory, Muted Group theory and Uses and Gratification theory, the study explores the potential audience and market, and the technological and financial viability of such a website. The study's findings show that, it is feasible and necessary to create a website for Chinese-literate women in the Philippines that would satisfy the audience's information needs as well as provide a voice for their ideas and experiences. Supporting this assertion are some of the study's major findings to wit: In the present Information Age and Globalization trends, the Chinese living in the Philippines, particularly the women, possess a strong desire for information and communication that the present Philippines Chilese-language media have not fully met. There is a potential audience market in the Philippines for the proposed website, despite the limitation posed by a foreign language. A significant number of this audiences belong to the Chinese community from Mainland China that is rapidly developing due to the greatly increasing cultural and economic relations between Mainland China and the Philippines. Compared with tradition media or channels, a website is more advantageous, since it contains more features that can serve the needs of this particular Chinese community in the Philippines. Not only can a website offer information, it vcan also connect this group to flourish as a community. The Internet offers abundant choices for its audience, as the latter uses of the Internet actively.In order to attract the audience's interest, a website must study the audience carefully, relate closely to their lives and be concerned with their needs. The results also indicate that women actively seek information in websites depending on their present needs and preferences. Their use of the website exceeds the usual content of "women's website", like beauty, child-raising and housekeeping. To serve women's information and communication needs, the proposed Chinese-language-based women's website should also expand its content to include a variety of topics and should avoid the stereotyping of women."